Epidemiological profile of people with intestinal ostomy at a referral center (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: to describe the epidemiological and clinical profile of people with intestinal stoma. Methods: documentary research, carried out in a reference center for people with disabilities in northeastern Brazil. Data collection was performed from December 2018 to February 2019, through a review of medical records. Results: there was a predominance of males (56.6%), average of 56.7 years, 41.4% married, 22.0% had incomplete elementary school, 27.9% had an income of 2 to 3 minimum wages, 47.1% were retired and 53.4% lived in the capital. Neoplasia was the main cause of stoma (62.2%) and colostomies corresponded to 84.4%, of which 38.3% were definitive. 60.3% had complications and 54.4% of them corresponded to periestomal dermatitis. Conclusion: people with intestinal colostomy were male, elderly, married, retired, with low schooling and definitive stoma due to neoplasia. Knowing the profile is essential to plan the reception, assist the treatment and rehabilitation of people with intestinal stoma.